Avaliação da qualidade de vida após a infecção por Sars-Cov-2 e a ocorrência da síndrome pós-Covid-19 em pacientes oncológicos - Pereira, Thamires Lira Fonsêca (2023)
Introduction: Covid-19 is an infection caused by the Sars-Cov-2 virus that leads to mild respiratory symptoms and can affect patients who are part of risk groups more aggressively. Among the patients who are included in the risk group are cancer patients. Currently, it is known that Covid-19 can leave sequelae: fatigue, headache and neurological symptoms are the most frequent and have been shown to affect the quality of life (QoL) of this group of patients. Objective: to evaluate the quality of life of cancer patients after Sars-Cov-2 infection and the occurrence of post-Covid-19 syndrome. Methodology: this is an observational, descriptive and cross-sectional study of a quantitative nature, carried out at the Napoleao Laureano Hospital. People over 18 years old with a cancer diagnosis, who underwent the RT-PCR test during the period from March 2020 to April 2022 were included in the study. The sample consists of all patients with data available in the medical record base and CCIH who agreed to participate in the study. Information related to the sociodemographic profile, diagnosis of Covid-19 and oncological diagnosis were collected from the patients' medical records, then the EORTC QLQ-C30 quality of life class was applied, an instrument that evaluates the quality of life in cancer patients and a contact related to post-Covid-19 symptoms. In order to obtain a comparison parameter, cancer patients who did not have Covid-19 were also included in the study. With the data collected, descriptive statistics were used, a Binary Logistic Regression model and a model based on the Weight of Evidence were standard. The study was approved by the Research Ethics Committee through opinion number 5.440.128. Results: 40 participants were included, 20 with a positive RT-PCR test for Covid-19 and 20 with a negative RT-PCR test. The average age of study participants was 56 years; more than 70% are female and live in João Pessoa. As for the oncological diagnosis, more than 50% of the participants had a breast cancer diagnosis. Regarding the assessment of QoL, participants who had Covid-19 had higher scores on the symptom and financial scales, while participants who did not have Covid-19 had higher scores on the functional scales and the global QoL scale. The fitted logistic regression model showed evidence that individuals who had Covid-19 are 83,6% less likely to have high QoL scores, individuals who have some comorbidity are 78,3% less likely to have high QoL scores and that for every 1-point increase in the values of the emotional scale, there is evidence of a 2,9% increase in the chance of having high QoL scores. 60% of participants who had Covid-19 reported having post-Covid-19 symptoms for more than 4 weeks. The model proposed by the weight of evidence demonstrated that the role performance scale variable proved to be the variable with the greatest weight of evidence to explain the QoL outcome. Conclusion: Cancer patients are exposed to several factors that can interfere with their quality of life in addition to the Covid-19 infection that can also influence this outcome. This way, the present study contributes to the understanding of the magnitude that the diagnosis of Covid-19 and the limitations caused by the oncological diagnosis itself can bring to the lives of affected individuals.